Micropatterned hydrogels and cell alignment enhance the odontogenic potential of stem cells from apical papilla in-vitro. Issue 1 (January 2020) - Ha, Michael; Athirasala, Avathamsa; Tahayeri, Anthony; Menezes, Paula P.; Bertassoni, Luiz E.
Highlights: Stem cells from the apical papilla (SCAPs) show increased spreading on hydrogel substrates with increased stiffness. SCAPs align along micropatterned substrates acquiring morphologies reminiscent of odontoblasts. Patterned substrate supported enhanced odontogenic differentiation when compared to non-patterned controls. Abstract: Introduction: An understanding of the extracellular matrix characteristics which stimulate and guide stem cell differentiation in the dental pulp is fundamental for the development of enhanced dental regenerative therapies. Our objectives, in this study, were to determine whether stem cells from the apical papilla (SCAP) responded to substrate stiffness, whether hydrogels providing micropatterned topographical cues stimulate SCAP self-alignment, and whether the resulting alignment could influence their differentiation towards an odontogenic lineage in-vitro. Methods: Experiments utilized gelatin methacryloyl (GelMA) hydrogels of increasing concentrations (5, 10 and 15%). We determined their compressive modulus via unconfined compression and analyzed cell spreading via F-actin/DAPI immunostaining. GelMA hydrogels were micropatterned using photolithography, in order to generate microgrooves and ridges of 60 and 120 μm, onto which SCAP were seeded and analyzed for self-alignment via fluorescence microscopy. Lastly, we analyzed the odontogenic differentiation of SCAP using alkaline phosphatase protein expression (ANOVA/Tukey α  = 0.05). Results: SCAP appeared to proliferate better on stiffer hydrogels. Both 60 and 120 μm micropatterned hydrogels guided the self-alignment of SCAP with no significant difference between them. Similarly, both 60 and 120 μm micropattern aligned cells promoted higher odontogenic differentiation than non-patterned controls. Significance: In summary, both substrate mechanics and geometry have a statistically significant influence on SCAP response, and may assist in the odontogenic differentiation of dental stem cells. These results may point toward the fabrication of cell-guiding scaffolds for regenerative endodontics, and may provide cues regarding the development of the pulp-dentin interface during tooth formation.